Generalization of Odd Ramos-Louzada generated family of distributions: Properties, characterizations, and applications to diabetes and cancer survival datasets - Okutu, John Kwadey; Frempong, Nana Kena; Appiah, Simon K.; Adebanji, Atinuke O. (Elsevier, 2024)
This article is published by Elsevier, 2024 and is also available at https://doi.org/10.1016/j.heliyon.2024.e30690